Oleogels with Birch Bark Dry Extract: Extract Saving Formulations through Gelation Enhancing Additives - Kashif Ahmad Ghaffar; Rolf Daniels (MDPI AG, 2020)
Triterpenes from the outer bark of birch have many beneficial biological and pharmacological activities. In particular, its wound healing efficacy is of paramount importance. Apart from that, particles of a birch bark dry extract aggregate into a three dimensional network when they are dispersed in lipids yielding a semi-solid oleogel. However, gel formation requires high amounts of the extract, which then acts at once as the active ingredient and the gelling agent. Infrared spectra of the respective mixtures proved that hydrogen bonds play a crucial role in the formation of the gel network. Dicarboxylic acids had almost no effect on gel strength. Monoalcohols increased the firmness of the oleogel with a decreasing effect from methanol > ethanol > butanol > octanol. All tested terminal diols increased the gel strength whereas vicinal diols affected the gel strength negatively. The effect was highly dependent on their concentration. The different effects of the diols are linked to their structure and polarity. The most pronounced enhancement of gelation was found for 1,6-hexanediol, which reduced the amount of triterpene extract (TE), which is necessary for the formation of an oleogel by a factor of 10.